The importance of determinants influencing FDI inflows within the CEE region - Pindžo, Renata; Vjetrov, Ana (Industrija, 2013)
In this paper, we examine the variables influencing FDI inflows in CEE countries and the sample includes fourteen countries within the CEE region. The variables analyzed in the paper are: financial sector development, human capital and physical infrastructure. Empirical analysis, presented in the paper, indicates that the countries with well developed capital markets can enhance the level of FDI inflows. Moreover, the same analysis points out a clear link between the total labor force related to a local market and FDI inflows. Finally, the correlation between physical infrastructure development and FDI inflows is set. In the end, creating stable and efficient business environment may influence a higher level of both foreign and domestic investments within the country.